Effects of firewood harvesting intensity on biodiversity and ecosystem services in shrublands of northern Patagonia - Goldenberg, Matías Guillermo (2020)
Fil: Goldenberg, Matías G. Universidad Nacional de Río Negro. Instituto de Investigaciones en Recursos Naturales, Agroecología y Desarrollo Rural; Argentina.